THE ROLE OF GOVERNMENT IN REVITALIZATION OF ISLAMIC SCHOOL IN TURKEY - jo, Rahar (WALISONGO, 2014)
Selama berabad-abad Islam telah menjadi agama negara di Turki. Tetapi ituberubah saat Turki mendeklarasikan diri sebagai negara Republik pada tahun1923. Turki menjadi negara sekuler dan membuat Islam tertekan. Namun saatsistem politik Pemerintah Turki mengadopsi multipartai dan partai itu kemudiandidukung oleh masyarakat Muslim dan memimpin pemerintahan, perlahankeberadaan Islam kembali tampak. Kondisi ini memengaruhi keberadaanpendidikan dan sekolah-sekolah Islam, yang pada dua dekade terakhir jumlahnyameningkat tajam. Penelitian ini mengumpulkan data tentang kontrol kualitaspendidikan, bentuk-bentuk pendidikan Islam dan peran pemerintah terhadappendidikan Islam. Melalui teknik dokumentasi, observasi dan interview, penelitianini menunjukkan bahwa: 1) kontrol kualitas pendidikan di Turki dilakukan dibawah kementerian pendidikan nasional; 2) bentuk sekolah dibagi menjadinegeri dan swasta, dan 3) peran pemerintah terhadap sekolah-sekolah Islamtidak dilakukan secara langsung, namun melalui kebijakan Kementerian PendidikanNasional yang diberlakukan secara umum kepada sekolah negeri.***Islam had been the religion of the state in Turkey for many centuries, but it wasdisappeared when the type of the state was changed into republic in 1923. Turkeythen has become a secular state and Islam has been depressed. However, when thepolitical system in Turkey adopted multiparty and the party supported by Muslimcommunity run the ruling government, Islam gradually has existed. This affected theIslamic education and schools, which have been sharply increased in number duringthe last 2 decades. This research was conducted to identify the quality control ofeducation, the types of Islamic education and the role of government towardsIslamic schools. By using techniques of documentation, observation and interview,this research indicated that: 1) the quality control of education in Turkey is doneunder ministry of national education; 2) the types of Islamic education are dividedinto public and private and 3) the role of government towards Islamic schools is notimplemented straight forward, but through the policy in the Ministry of NationalEducation addressed towards the public schools.Keywords: quality control of education, Ä°mam Hatip school, role ofgovernment